Formal and Informal Language Used by Hana Miyakoshi in www.Working!! Anime Episode 1 Produced by Aniplex - Rahmad Novianto Ardiansyah (Balai Bahasa Kalimantan Tengah, 2019)
The Japanese language have four levels of language formality. The languages classified as Kenjogo (humility language), Sonkeigo (honorific language), Teineigo (usual formal language), and the last is Futsugo (daily language). The formalities in the Japanese language also shown in Japanese animation, anime. This study researched the utterance by Hana Miyakoshi in Aniplex anime titled www.working!! episode I. This research focuses on discovering what type of and how Hana Miyakoshi utters the Japanese language used in the anime. This study is a descriptive qualitative study. The result of this study is there are 11 data of Hana Miyakoshi utterances. Those 11 is consisting of 3 formal variants and 8 informal variants. Hana Miyakoshi uses a Japanese formal variant when attending the costumer of Wagnaria, and she uses the informal variant of Japanese language when she is communicating with her coworker.